(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article examines the performativity of the reproduction of performance through a bibliographic review that initially passes through the establishment of a parallel between the Austian notion of performative and the Deleuzian concept of event. The analysis follows through adjustments proposed by Fischer-Lichte, Goffman, Butler and Colling to locate the performative power in the presential performance in a more distinct way. Finally, we seek to highlight a corresponding power in the context of the reproduction of performances using the positivity of the concept of simulacrum proposed by Deleuze and commentators.